Synthesıs and in Sılıco Studıes of 1,3,5-Trıaryl-2-Pyrazolıne Derıvatıves Contaınıng Chloro Substıtuent and Pyrrolıdıne Moıety - Jasril, Jasril; Iktiarudin, Ihsan; Ulhukmi, Nisa; Novianty, Riryn; Syaifullah, Mhd Muslim; Frimayanti, Neni (Molekul, 2026)
ABSTRACT. Pyrazoline is a well-known group of five-ring heterocyclic compound containing two nitrogen atoms that has a wide range of promising biological activities. The aim of this research is to synthesize 1,3,5-triaryl-2-pyrazoline derivatives with chloro substituent and pyrrolidine moiety and to explore their potency as inhibitors for cervical cancer. The synthesis was performed through three-steps reactions. Firstly, synthesis of chlorinated naphthalenyl chalcones through Claisen-Schmidt condensation. Secondly, synthesis of chlorinated naphthalenyl pyrazolines through nucleophilic addition of phenylhydrazine to the chalcone and followed by intramolecular cyclization. Thirdly, synthesis of pyrazoline derivatives by adding the pyrrolidine moiety through O-alkylation reaction. Then, the in silico studies through molecular docking, ADME profiling, and toxicity prediction were performed to explore the potency of the synthesized compounds as inhibitors of cervical cancer by inhibiting the activity of Sirtuin-1 (SIRT-1) (PDB ID: 4I5I). The structure of all pyrazoline derivatives (4a-4c) were confirmed by spectroscopic analysis including UV, FT-IR, HRMS, and NMR. Based on the docking study, compound 4a with binding free energy of -12.59 kcal/mol exhibited better potency as SIRT-1 inhibitor than previously reported inhibitor (EX527). Then, based on the ADME profiling and toxicity prediction, it can be concluded that compound 4a exhibited reasonable drug properties with low toxicity potency (predicted LD50 = 1000 mg/kg). Keywords: : Cervical cancer, molecular docking, pyrazoline-pyrrolidine, pyrazoline synthesis, sirtuin-1